Optical, electromagnetic and physiochemical properties of flower-like MoS2 (D) and Ni microsphere (M) based absorbers for X and Ku band applications. Issue 2 (15th January 2022) - Lin, Yinhe; Akhtar, Majid Niaz; Abu-Hamdeh, Nidal H.; Bezzina, Smain; Tan, Hoi Huynh; Wang, Zhe
Abstract: Currently, absorbing materials with thin thickness, lightweight, and strong absorption are required to reduce electromagnetic pollution. Flower-like MoS2 (D) and Ni microsphere (M) with MoS2 (D/M) absorbers were successfully fabricated via hydrothermal and solvothermal methods. Structural, physiochemical, elemental, and magneto-optical studies of the D and D/M samples were evaluated. The bandgap for M, D, and D/M composite is 2.56 eV, 3.1 eV, and 3.7 eV respectively. Morphological studies confirm the shape of the Ni microsphere and flower-like structure of the MoS2 composite. D and D/M composite show synergistic performance in terms of effective bandwidth, absorption, and reflection loss. The RL from D is −24.5 dB for 1.5 mm thickness whereas the D/M sample shows −9 dB at 2.5 mm thickness. Double layer absorbers of D and D/M were simulated using CST software. The lower/upper layer of D and D/M with 1.5 mm lower and 0.5 mm upper layers' arrangement depicted minimum reflection loss and depicted their use for Ku band application. Therefore, D and D/M composites with thin thickness and minimum reflection loss might be suggested for application in microwave absorption.